Peningkatan Kemampuan Bernalar Kritis Melalui Model PBL Berbasis Kearifan Lokal pada Mata Pelajaran Pendidikan Pancasila Kelas III SDN Sendangmulyo 02 Kota Semarang - Safitri, Desyana Ajeng Safitri; Ariestika Damayani; Khusnul Fajriyah; Arum Rismawati (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the critical thinking skills of third-grade students at SDN Sendangmulyo 02 Kota Semarang through the implementation of the Problem Based Learning (PBL) model based on local wisdom in the Pancasila Education subject. The main problem identified was the low engagement of students and their underdeveloped critical thinking abilities. This Classroom Action Research (CAR) was conducted in two cycles using both test and non-test data collection techniques (observation and documentation). The results showed a significant improvement in students’ critical thinking skills. The average student score increased from 57 in the pre-cycle to 67 in the first cycle and 85 in the second cycle. The percentage of learning mastery increased from 21% to 82%. The implementation of the PBL model based on local wisdom was proven to be effective in enhancing students' critical thinking skills, making learning more meaningful and contextual.